Memory, Anniversaries and Mental Health in International Historical Perspective
XVI, 314 p. 13 illus., 12 illus. in color.
Keywords: This book is the first to explore memory, misremembering, forgetting, and anniversaries in the history of psychiatry and mental health. It challenges simplistic representations of the callous nature of mental health care in the past, while at the same time eschewing a celebratory and uncritical marking of anniversaries and individuals. Asking critical questions of the early Whiggish histories of mental health care, the book problematizes the idea of a shared professional and institutional history, and the abiding faith placed in the reform of medicine, administration, and even patients. It contends that much post-1800 legislation drafted to ensure reform, acted to preserve beliefs about the ‘bad old days’ and a ‘brighter future’ in the state memories of imperial powers, which in turn exported these notions around the world. Conversely, the collection demonstrates the variety of remembering and forgetting, building on recent interest in the ideological and cultural linkages between pastand present in international psychiatric practice. In this way, it seeks to trace the pathways of memory, exploring the direction of travel, and the perpetuation, remodeling, and uprooting of recollection. Chapter “The New Socialist Citizen and ‘Forgetting’ Authoritarianism: Psychiatry, Psychoanalysis, and Revolution in Socialist Yugoslavia” is available open access under a Creative Commons Attribution 4.0 International License via link.springer. com. Rebecca Wynter is a historian at the Universities of Amsterdam and Birmingham. She has published widely on the histories of psychiatry, mental health, neurology, first response, and so-called ‘conversion therapy’. She is active in public history, working with museums, institutions and people to reveal the past. Jennifer Wallis is a Medical Humanities Teaching Fellow and Lecturer in the History of Science and Medicine at Imperial College London, UK. She has published widely on the nineteenth-century asylum and the history of medicine in the Victorian period. Rob Ellis is a Reader in History at the University of Huddersfield, UK. He has published widely on the histories of mental ill-health and learning disability and has worked in partnership to co-produce projects that have emphasized their contemporary relevance. .